3D plasma metal deposition for processing multi material Titanium parts. Issue 1 (4th March 2021) - Hoefer, Kevin
ABSTRACT: Within this study, the potential of 3D Plasma Metal Deposition (3DPMD) for the additive manufacturing of multi-material metallic parts in layerwise design is presented. For this purpose, a demonstrator geometry with a step-wise increase of the tungsten carbide content in a Ti6Al4V matrix was fabricated. The build cycle itself, the component shape and the microstructure were investigated. The analysis of the macroscopic properties was performed by optical microscopy and scanning electron microscopy. In summary, 3DPMD offers the possibility to produce AM parts at high build rates and increased material flexibility. The analysis of the morphology and the macroscopic investigations shows a homogenous structure without defects. The carbide content of the manufactured components increases continuously from 0 to 12 vol.% but deviates from the aimed carbide content. Using automated CAM routines, it is possible to generate metallic multi-material structures using welding robots directly from the CAD drawings.